Social Media in Language and Literature - Haripriya SK; Akshaya Baskar (International Journal of Scientific Research in Science and Technology, 2024)
The advent of social media has significantly impacted the fields of language and literature, altering how we communicate, create, and consume content. This research paper explores the multifaceted influence of social media on language evolution and literary expression. Social media platforms have introduced new forms of language, characterized by brevity, informality, and the use of emojis and acronyms. These linguistic innovations have permeated everyday communication and literary works, reflecting contemporary modes of interaction. Additionally, social media has democratized the literary landscape, providing a platform for diverse voices and fostering a global literary community. This study examines how authors leverage social media for storytelling, audience engagement, and the promotion of literary works. By analyzing various case studies and literary texts, the paper highlights the transformative role of social media in shaping modern language and literature, emphasizing its potential to influence future literary trends and linguistic developments. Building on the exploration of social media’s impact, this paper further delves into how digital platforms have reshaped literary forms, such as the rise of micro-fiction, digital poetry, and interactive storytelling. Social media has also given rise to collaborative writing projects and fan fiction communities, allowing readers to become active participants in the creative process. Additionally, the paper investigates how viral trends and hashtags influence literary themes, enabling works to reach global audiences quickly. The study concludes by discussing the challenges social media poses for traditional publishing and how it paves the way for innovative forms of literary expression in the digital age.
Keywords: Pros; Interpretive criticism; Problems; Appraisals; Demerit; Leverage